Should religious beliefs be allowed to stonewall a secular approach to withdrawing and withholding treatment in children?. Issue 9 (30th March 2012) - Brierley, Joe; Linthicum, Jim; Petros, Andy
Abstract : Religion is an important element of end-of-life care on the paediatric intensive care unit with religious belief providing support for many families and for some staff. However, religious claims used by families to challenge cessation of aggressive therapies considered futile and burdensome by a wide range of medical and lay people can cause considerable problems and be very difficult to resolve. While it is vital to support families in such difficult times, we are increasingly concerned that deeply held belief in religion can lead to children being potentially subjected to burdensome care in expectation of 'miraculous' intervention. We reviewed cases involving end-of-life decisions over a 3-year period. In 186 of 203 cases in which withdrawal or limitation of invasive therapy was recommended, agreement was achieved. However, in the 17 remaining cases extended discussions with medical teams and local support mechanisms did not lead to resolution. Of these cases, 11 (65%) involved explicit religious claims that intensive care should not be stopped due to expectation of divine intervention and complete cure together with conviction that overly pessimistic medical predictions were wrong. The distribution of the religions included Protestant, Muslim, Jewish and Roman Catholic groups. Five of the 11 cases were resolved after meeting religious community leaders; one child had intensive care withdrawn following a High Court order, and in the remaining five, all Christian, no resolution was possible due to expressed expectations that a 'miracle' would happen.